Relationship Between Sociodemographic Factors and Health Literacy Levels in Sleman Regency - Faadhilah, Muflih (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to determine the relationship between sociodemographic factors and health literacy levels in Sleman Regency. Methods: This quantitative cross-sectional study utilized secondary data from the Health and Demographic Surveillance System (HDSS) in Sleman. Data collection was based on the HLS-EU-Q16 questionnaire. Data analysis was conducted using logistic regression analysis with a significance level 0.05. Results: Bivariate analysis revealed that age (p-value 0.000), education (p-value 0.000), and occupation (p-value 0.000) were significantly related to health literacy levels. However, gender (p-value 0.829) and residential location (p-value 0.516) were not significantly related to health literacy levels. Conclusion: Sociodemographic factors related to health literacy levels include age, education, and occupation.